2009
DOI: 10.1897/08-296.1
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a Daphnia magna four-day survival and growth test method

Abstract: Zooplankton are an important part of the aquatic ecology of all lakes and streams. As a result, numerous methods have been developed to assess the quality of waterbodies using various zooplankton species. Included in these is the freshwater species Daphnia magna. Current test methods using D. magna involve acute lethality test methods ranging from 24 to 96 h in duration and chronic test methods with durations of 21 to 28 d. Whereas the current acute and chronic test methods are useful, a need exists for a shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
(26 reference statements)
0
17
0
Order By: Relevance
“…The 4-day D. magna studies, initiated with \24-h old organisms, were performed following methods employed in the 21-day chronic study previously conducted (Naddy et al 2007a) and as modified from Lazorchak et al (2009). Two static-renewal (daily) studies were performed with two different food types to determine how they affected silver toxicity.…”
Section: Test Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 4-day D. magna studies, initiated with \24-h old organisms, were performed following methods employed in the 21-day chronic study previously conducted (Naddy et al 2007a) and as modified from Lazorchak et al (2009). Two static-renewal (daily) studies were performed with two different food types to determine how they affected silver toxicity.…”
Section: Test Methodsmentioning
confidence: 99%
“…In the chronic studies, the C. dubia was less sensitive than D. magna (Naddy et al 2007a). Given this change in sensitivity between no food and food exposures, we compared the relative mitigating ability of the different food types using a single test method: the 4-day D. magna short-term chronic study developed by Lazorchak et al (2009). Using this method, we observed that, indeed, the C. dubia food had a higher degree of mitigating ability for Ag compared to the D. magna food (Fig.…”
Section: Invertebrate Studiesmentioning
confidence: 99%
“…The bioassay was conducted according to the OECD guideline 202 [14]; however, the study duration was set to 72 h, because extensions in time are proposed for general chemical testing with D. magna [19]. Control mortalities remained at 0%.…”
Section: Acute Toxicity Testmentioning
confidence: 99%
“…In contrast to most previous acute toxicity tests using nTiO 2 and D. magna , a 96-h exposure was used instead of the standard 48-h test duration, which hardly ever showed effects on D. magna [6]. Such a 96-h toxicity test setup with D. magna using mortality and growth as endpoints has previously been suggested for general chemical testing [18]. Moreover, a recent study showed an increased toxicity of nTiO 2 following an exposure of 72 h [9], illustrating the potential of a prolonged acute test duration.…”
Section: Introductionmentioning
confidence: 99%